GANTI KERUGIAN DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL BOGOR RING ROAD SEKSI II B - Dewi, Rose Rostisa; Kusbiantoro, -; Saiman, Ridwan (E-Journal Widya Yustisia, 2020)
Land is a basic human need in life and life. Land is one of the main natural resources which has an inner value and has a strategic value in meeting the needs of life. Development as an implementation of the state objectives formulated in the 1945 Constitution requires land. This study aims to determine how the implementation of compensation in land acquisition for the construction of Ring Road Section II B Toll road. The method used in this study is the Juridical Normative, the data is obtained from the results of library research in the form of statutory regulations, scientific writings of experts to describe issues discussed. Compensation for land acquisition for the construction of Ring Road Section II B toll road is a reasonable and fair compensation including physical compensation for construction, plants. Non-physical replacements in the form of solutions, waiting periods, BPHTP tax incentives, PPAT fees and assessments carried out by an independent public service. It can be concluded that the compensation received by the land owner used for the construction of Ring Road Section II B toll road is in accordance with the rules in Law No. 2 of 2012 concerning land acquisition for development and public interest.